A Study of English Listening and Speaking Abilities of 1st Graders Using Total Physical Response Method - พละโชติ, ศิริพร; เนาวนนท์, อดิศร (Ratchaphruek Journal, 2018)
The purposes of this research were to compare 1) English listening abilities of 1st graders before and after learning using total physical response method, 2) English listening abilities of 1st graders using total physical response method after a learning percentage of 70 with in the criterion, 3) English speaking abilities of 1st graders before and after learning using total physical response method, and 4) English speaking abilities of 1st graders using total physical response method after a learning percentage of 70 with in the criterion. The research sample was 34 students, who were from Ban Khaodin School, in 2017 academic year Klonghat District, Sakaeo Province, receive by cluster random sampling. The research instrument comprised; lesson plans with total physical response, an English listening ability test, and an English speaking ability test. Statistic for data analysis were the percentage, mean ( ) Standard Deviation (S.D.) and t-test. Research findings showed that: 1. English listening abilities of 1st graders whereas before learning the lessons, = 2.32, S.D. = 1.01; after learning the lessons, = 7.85, S.D. = 1.42; and improvement score = 5.53, S.D. = 1.44, after learning the lessons, English listening score was higher than before at .05 level. 2. English speaking abilities before learning the lessons, = 7.53, S.D. = 2.02; after learning the lessons, = 21.94, S.D. = 2.62; and improvement score = 14.41, S.D. = 3.36 after learning the lessons, English speaking score was higher than before at .05 level. 3. After learning the lessons, English listening and English speaking abilities of 1st graders were significantly higher than 70% criterion at the .05 level.